USULAN PERBAIKAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) SEBAGAI UPAYA MEMINIMALISIR ANGKA KECELAKAAN KERJA MENGGUNAKAN METODE HAZOP (Studi Kasus : PT. XYZ) - Muhammad Nur (LPPM ITK, 2019)
PT. XYZ is a company engaged in oil palm plantations and processing with its main commodity is the oil palm plantations (Elais Queineensis Jack). In 2018, thare are several occupational safety and health problems naamely occupational accidents experienced by special employees in the production processarea. The purpose of this study is to detemine the types of work accidents, the types of hazards created based on the risk materics. This study begins by identifying Hazard and risk and then looking for potential sources of occuptional hazard so that harm can be done using the Hazard and Operability Study (HAZOP) method. The research results have been carried out based on the process (Crude Palm Oil) found 8 sources of potential danger between : Loding Ramp Station, Sterilizer Station, Tippler Station, DigesterStation, Press Station, Clarification Station, Kernel Stationdan Boiler Station, then risk assessment : low risk, medium risk, high risk and extreme risk.